Open Public Vocational School Data for Germany - Loll, Ines (My University, 2026)
"Public dual vocational schools in Germany as of 2025 were systematically modelled as individual Wikidata items linked to their offered training occupations and corresponding German occupational codes (KldB). Registries from all 16 federal states were harmonised and enriched with school website information. Each item includes geographical coordinates, training occupations, the person the school is named after (if applicable), multi-campus structures, and external identifiers. A total of 1,442 vocational school items are available on Wikidata and as a curated dataset on Zenodo. The vocational school dataset supports spatial analyses, including commuting patterns and regional coverage of training occupations, and it allows studies on school naming." (Author's abstract ; BIBB-Doku)
Keywords: S 3.1.2.1 Berufliche Teilzeitschulen, Berufsschulen; 370; Berufsbildende Schule; Berufsschule; Bundesrepublik Deutschland; Ausbildungsberuf; Berufsklassifikation; Forschungsdaten